Psychosocial impact, perceived stress and learning effect in undergraduate dental students during transition from pre-clinical to clinical education - Frese, Cornelia; Saure, Daniel; Staehle, Hans Jörg (European journal of dental education, 2018)
Introduction This study aimed to develop a suitable instrument for a comprehensive quantitative and qualitative assessment of perceived psychosocial impact, levels of stress and learning effect in undergraduate dental students during the transition from pre-clinical to clinical education. These findings might improve curricular structures and didactic organisation during this period. Materials and methods At the beginning of their first clinical year, undergraduate dental students were asked to complete an anonymous forty-item questionnaire. Two hundred and seventy-six undergraduate dental students were willing to participate and completed the questionnaire and participated during the years 2011-2016. Results The response rate was between 45% and 96%. Correlational analysis (Spearman-Rho) in the field of psychosocial impact showed the dental teacher to be the most important multiplier of students' feelings. If the students feel that their teacher acts cooperatively, positive items increase and negative items decrease significantly (P < .0001). Also, students who report high levels of stress are affected significantly in their psychosocial interaction (P < .0001). Wilcoxon test yielded highest levels of stress in endodontology during the first weeks (P < .0001). During the same period, the greatest learning increment was seen for diagnostics and caries excavation. Conclusion In conclusion, teaching of undergraduate dental students during the transition period from pre-clinical to clinical education can be positively influenced by a supportive learning environment and by specific chronological modifications in the curriculum. Students should start their clinical training with diagnostics, preventive dentistry and initial periodontal treatment. Due to high levels of perceived stress, endodontology should be introduced later in the clinical curriculum.
Gesehen am 23.07.2019